Determinants of the Foreign Exchange Risk Premium in Gulf Cooperation Council Countries - Poghosyan, Tigran (IMF Working Papers; Working Paper ;, 2010)
This paper analyzes macroeconomic determinants of the foreign exchange risk premium in two Gulf Cooperation Council (GCC) countries that peg their currencies to the U.S. dollar: Saudi Arabia and the United Arab Emirates. The analysis is based on the stochastic discount factor methodology, which imposes a no arbitrage condition on the relationship between the foreign exchange risk premium and its macroeconomic determinants. Estimation results suggest that U.S. inflation and consumption growth are important factors driving the risk premium, which is in line with the standard C-CAPM model. In addition, growth in international oil prices influences the risk premium, reflecting the important role played by the hydrocarbon sector in GCC economies. The methodology employed in this paper can be used for forecasting the risk premium on a monthly basis, which has important practical implications for policymakers interested in the timely monitoring of risks in the GCC.